Board Attribute and financial performance of Sri Lanka. Does firm size matter? - Tharsika, K.; Thaneshan, G.; Varanitha, S. (University of Jaffna, 2024)
Purpose: There have been plenty of studies on the link between board attributes and company financial performance, nevertheless, none of them have particularly explored the moderating influence of the firm size in this nexus in terms of the developing nation Sri Lanka. Therefore, the objective of this research is to examine the moderating effect of firm size on the relationship between board attributes and the financial performance of listed companies in Sri Lanka. Design/Methodology/Approach: Return on Assets (ROA) is utilised to evaluate the firm performance, while board attributes include board size, independence and board meetings. This study utilises panel data from 100 non-financial listed firms in Sri Lanka to investigate the relationship during the period spanning from 2019 to 2023. Findings: The Hausman test and Breusch and Pagan Lagrangian multiplier test indicate that the random effect model is more favorable than the fixed effects model or pooled ordinary least squares regression model. The results of random effect model demonstrate that the inclusion of firm size as a moderating variable has solely had a negative impact on the link between board size and ROA. The presence of firm size does not significantly affect the relationship between board independence and meeting and ROA. Research limitations: The study exclusively examined reports from a five- year period for certain non-financial companies listed on the CSE in order to assess the study objective. This study only considers the board attributes in governance structures such as board independence, board size and board meeting and also ROA used to measure the performance. Implications: This study contributes empirical evidence to the insufficiently studied association between board attributes and financial performance as moderated by firm size. Further, this study's results are to support managers of the firm, legislators, and regulators in determining the board characteristics and the firm size of the business.
Keywords: Board attribute; Financial performance; Firm size; Moderating effect; Sri Lanka